Marvel's Spider-Man, Miles Morales : the art of the game - Ralphs, Matt; Insomniac Games, Inc.; Sony Interactive Entertainment America LLC. (London : Titan Books, 2021)
Official art book of the PS5 launch game Marvel's Spider-Man: Miles Morales, featuring concept art created during the development of the game. Be greater, be yourself as Miles Morales swings onto the scene in his own video game for the first time. Learning the ropes as Spider-Man in Peter Parker's absence, Miles must find the balance between keeping his new home, Harlem, safe and rising up to take on new challenges and enemies that test his abilities and loyalties to the limit. The creative process of this much-anticipated game is captured in Marvel's Spider-Man: Miles Morales - The Art of the Game. This lush, hardback book showcases the remarkable concept art and in-game renderings created by the talented development team creating the game in collaboration with Marvel. Characters, locations, tech, gadgets, Spider suits and much more are presented in all their incredible detail, accompanied by unique insights from the artists and developers behind the game.
'What does Miles Morales mean to you?' -- Introduction -- Meet Miles Morales -- Being Spider-Man -- Deal with the Devil -- Fight for what you love.
Keywords: Morales, Miles -- (Fictitious character); Spider-Man -- (Fictitious character); Marvel's Spider-Man: Miles Morales (Video game) -- Pictorial works; Video games -- Pictorial works. -- Design; Video games in art; Computer art; Superheroes; Good and evil; Comic strip characters